2018
DOI: 10.1136/bmjopen-2017-018180
|View full text |Cite
|
Sign up to set email alerts
|

Trends in initiation of direct oral anticoagulant therapies for atrial fibrillation in a national population-based cross-sectional study in the French health insurance databases

Abstract: ObjectiveUnlike several other national health agencies, French health authorities recommended that the newer direct oral anticoagulant (DOAC) agents only be prescribed as second choice for the treatment of newly diagnosed non-valvular atrial fibrillation (NVAF), with vitamin K antagonists (VKA) remaining the first choice. We investigated the patterns of use of DOACs versus VKA in the treatment of NVAF in France over the first 5 years of DOAC availability. We also identified the changes in patient characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 38 publications
7
37
0
1
Order By: Relevance
“…The ESC guidelines for AF treatment encourage OAC treatment in high‐risk AF patients, and the introduction of NOACs that are safer and more comfortable for patients probably contributed to this increase in OAC use. In fact, multiple other studies mostly from Europe and the United States have attested to the rapid and massive adoption of all NOAC drugs in recent years 12,18,19,25‐34 . It is, thus, important to add data from different world regions to this literature.…”
Section: Discussionmentioning
confidence: 99%
“…The ESC guidelines for AF treatment encourage OAC treatment in high‐risk AF patients, and the introduction of NOACs that are safer and more comfortable for patients probably contributed to this increase in OAC use. In fact, multiple other studies mostly from Europe and the United States have attested to the rapid and massive adoption of all NOAC drugs in recent years 12,18,19,25‐34 . It is, thus, important to add data from different world regions to this literature.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Indeed, the choice of anticoagulant in patients with multiple conditions is complex. Recent data suggest that physicians are more likely to prescribe DOACs to healthier patients with fewer comorbidities, 12 while higher CHA 2 DS 2 -VASc and HAS-BLED scores are associated with lower probability of DOAC prescription compared with warfarin. 13 Our findings of similar effectiveness of all 3 anticoagulants for stroke prevention are assuring and will lend confidence to clinicians regarding DOAC use even in complex patients.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 11 Despite their increasing use, studies reveal that DOACs are more likely to be initiated in healthier patients with fewer comorbidities. 12 , 13 High-risk patients with MCC not only have higher stroke and bleeding risk, but also make up to 50% of newly diagnosed patients with AF. 9 Therefore, it is critically important to understand the efficacy and safety of DOACs in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the convenience of DOACs over warfarin, such as the needlessness of anticoagulation monitoring and less food interactions, DOACs are widely used in clinical settings instead of the conventional anticoagulant treatment, warfarin. Huiart et al reported that 61% of AF patients initially used one of the four DOACs as their anticoagulation therapy [9].…”
Section: Introductionmentioning
confidence: 99%